2015
DOI: 10.3126/ajms.v7i2.13135
|View full text |Cite
|
Sign up to set email alerts
|

Normative data of Visual Evoked Potential in children and correlation with age

Abstract: Background: Visual Evoked Potential is the assessment of the visual pathway and the visual cortex. The present study was descriptive analysis of normal VEP between the age of 6 months to 4 years of age and the determination of the neuronal development among healthy children of above age group. Materials and Methods: The study was conducted in neurological lab of BPKIHS on healthy children (n=36) of well-baby clinic between the age of 0.5 to ≤4 years (yr). Subjects were divided into subgroup 1(0.5 to ≤2 yr), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…A total 59 students of Mashhad University of Medical Sciences (32 females and 27 males) participated in this study. Since the morphologic and metabolic maturation of the visual cortex completes at the age of 18 and VEPs components are not affected after this age,19, 20 we selected participants who were 18 years and older (22.55 ± 3.79 years old). All participants had normal general and ocular health and their best-corrected visual acuity was 6/6 or better in each eye at 6 m. The procedures of this study were approved by the local Human Research Ethics Committee and were in conformity with the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total 59 students of Mashhad University of Medical Sciences (32 females and 27 males) participated in this study. Since the morphologic and metabolic maturation of the visual cortex completes at the age of 18 and VEPs components are not affected after this age,19, 20 we selected participants who were 18 years and older (22.55 ± 3.79 years old). All participants had normal general and ocular health and their best-corrected visual acuity was 6/6 or better in each eye at 6 m. The procedures of this study were approved by the local Human Research Ethics Committee and were in conformity with the Helsinki Declaration.…”
Section: Methodsmentioning
confidence: 99%
“…The latency values of VEPs for large checks and small checks reached adult levels respectively at 1 and 5 year of age 20 and the amplitudes of VEPs were not affected by age after 1 years 22, 23. Moreover, most studies have reported that the maturation of the visual pathway occurs around 4 years of age 20, 22, 24…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The study was conducted on 34 (19 1. The mean age of the control children was slightly higher than the study children, though not statistically significant (p=0.217).…”
Section: Resultsmentioning
confidence: 99%